Performance prediction and evaluation on the first balanced energy networks (BEN) part I: BEN and building internal factors. (15th April 2021) - Wang, Yang; Gillich, Aaron; LU, Daisy; Saber, Esmail Mahmoudi; Yebiyo, Metkel; Kang, Ren; Ford, Andy; Hewitt, Mark
Abstract: Approximately half of all energy consumed is used for generating heat and hot water in the UK, meanwhile, space heating and hot water consist of about 21% of greenhouse gas emissions. One pathway of decarbonizing heat is electrification of heat, the requirement of electricity is then met through smart grid and demand side response management. A new method for electrifying heat through a balanced energy network (BEN) system, which is situated in central campus of London South Bank University, has been presented. The validations of BEN model are performed against historic measurement data and manufacturer performance data. BEN system performance is then predicted and evaluated through investigating the effects of BEN and building internal factors including system operation mode, thermal storage, indoor set-point temperature, and COP of heat pump. Several key results were drawn as follows: (1) Carbon emissions from building energy consumption mainly depend on operation mode and thermal storage capacity of BEN system, actual heat demand in buildings and carbon emission factor as a function of time; (2) Energy consumption and costs and its carbon emissions will nonlinearly increase with the increasing of indoor set-point temperature; (3) In January (the coldest month of the year), the heating consumption for operating BEN system will be decreased by 77.9%/72.9% compared with historic monitoring data of 2014/2015; (4) For BEN system, the usage, costs and carbon emissions of electricity supplying to heat pump is an decreasing function of COP. Highlights: Prediction & Evaluation on system performance for a Balanced Energy Network in London. BEN system performance jointly solved by measurements and simulations. Diverse effects of internal factors of BEN & Buildings on system performance. Carbon emissions depending on operation mode, thermal storage capacity & real heat demand. Heating consumption decreased by 77.9%/72.9% for BEN comparing to 2014/2015 data.